1978
DOI: 10.1103/physrevlett.41.635
|View full text |Cite
|
Sign up to set email alerts
|

Observation of theα-Particle Breakup Process atEαlab=172.5

Abstract: 6 A thorough review of the general features of strongly damped collisions is contained in W. U. Schroder and J e R. Huizenga, Annu. Rev. Nucl. Sci. 2_7, 465 (1977).In connection with preequilibrium reaction theories, there has been growing interest in the study of continuous spectra of particles emitted in nuclear reactions. In the present investigation spectra of 3 He particles emitted in reactions induced by 172.5-MeV a particles on 58.eo.62.64 Ni targets have been studied in the energy range from 50 to 160 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 11 publications
5
63
1
Order By: Relevance
“…This reaction mechanism has been investigated by various authors, in particular Holmgren et al [11,12] and Budzanowki et al [13,14]. These studies revealed that in most cases one fragment is emitted with roughly unchanged velocity, while the other is absorbed by the nucleus.…”
Section: Binary Fragmentation Of the Alphamentioning
confidence: 92%
“…This reaction mechanism has been investigated by various authors, in particular Holmgren et al [11,12] and Budzanowki et al [13,14]. These studies revealed that in most cases one fragment is emitted with roughly unchanged velocity, while the other is absorbed by the nucleus.…”
Section: Binary Fragmentation Of the Alphamentioning
confidence: 92%
“…The aim of these theories was to derive closed-form formulas, in which the sum over final states of the x + A system is formally reduced to some expectation value of the imaginary part of the x + A optical potential. In the pioneering works by Baur and coworkers [23][24][25], the sum is done making use of unitarity and a surface approximation of the form factors of excited states of the residual nucleus. These two approximations were avoided in later works by Udagawa and Tamura [26,27], who used a prior-form DWBA formalism, and by Austern and Vincent [28], who used the post-form DWBA.…”
Section: Introductionmentioning
confidence: 99%
“…As an example of what appears to be fragmentation, we consider first the neutron spectrum [9] from 62Ni(c~,3He), measured at E~=173MeV and 0, = 5.9 ~ In the GeV energy range, where data of this type have been available for a few years and are firmly believed to represent fragmentation, it has been found empirically that the spectra are quite well fit by a Gaussian in the observed particle's momentum. This is equivalent to approximating the projectile wave function by…”
Section: Comparison With Experimentsmentioning
confidence: 98%
“…A fit to data of this type at p~ = 1 -3 GeV/c [10] yielded a=0.25Fm -1, which for the 173-MeV cds of Ref. 9 gives the prompt-fragmentation spectrum shown* in Fig. 4.…”
Section: Comparison With Experimentsmentioning
confidence: 99%